2016
DOI: 10.1007/s10877-016-9877-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of prolonged ischemia on human skeletal muscle microcirculation as assessed by near-infrared spectroscopy

Abstract: Near-infrared spectroscopy (NIRS) has been used to detect in vivo microvascular alterations by means of a vascular occlusion test. We sought to analyse by NIRS the microcirculatory profile of patients undergoing prolonged tourniquet-induced bloodless condition for extremity surgery, and compare the results with time of ischemia and comorbidities. We conducted a prospective observational study on 42 patients undergoing upper limb surgery. Regional anaesthesia was achieved and ischemia was induced by a tournique… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 44 publications
0
8
1
Order By: Relevance
“…These results indicate that the duration of ischemia has an influence on a possible hyperemic response. Tujjar et al showed that the hyperemic peak of the treated upper extremity measured using NIRI was also lower in patients with a longer duration of ischemia [ 26 ]. Reactive hyperemia in healthy volunteers was shown as a significant increase in the regional oxygen saturation above the initial values after release of an upper arm tourniquet ischemia [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results indicate that the duration of ischemia has an influence on a possible hyperemic response. Tujjar et al showed that the hyperemic peak of the treated upper extremity measured using NIRI was also lower in patients with a longer duration of ischemia [ 26 ]. Reactive hyperemia in healthy volunteers was shown as a significant increase in the regional oxygen saturation above the initial values after release of an upper arm tourniquet ischemia [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to others [ 26 ], we evaluated the influence of the tourniquet ischemia under local anesthesia to avoid the possible influence of plexus anesthesia on tissue oxygen saturation. As already described, the use of plexus anesthesia or the perioperative placement of a plexus catheter leads to an increase in local blood flow to the ipsilateral upper extremity and to vasodilatation [ 37 , 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…General anesthesia offers certain advantages, such as airway integrity, maintenance of ventilation in accordance with physiological conditions, sensitive control of anesthetic agent concentration through monitorization, the opportunity to make rapid changes to anesthetic levels, and rapid awakening (Corcoran et al, 2006). That said, the technique also comes with certain disadvantages, including postoperative symptoms such as nausea-vomiting, while in cases receiving inhalation anesthesia, blood flow can be reduced in the flap, negatively affecting flap viability (Ederer et al, 2020;Seal et al, 2011;Tujjar et al, 2017;Lee at al., 2020), and postoperative pain can lead to vasospasm (Lanz et al, 2001;Banic et al, 1997). For such reasons, flap perfusion may be adversely affected (Adolphs et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…In another study by Tujjar in the June 2017 issue of this journal [10], the evolution of StO 2 following a rather extensive “VOT” was analyzed. First, for patients who underwent extremity surgery, regional anesthesia was provided, which was associated with a rise in StO 2 .…”
Section: Near Infrared Spectroscopymentioning
confidence: 99%